1971
DOI: 10.1017/s0252921100048922
|View full text |Cite
|
Sign up to set email alerts
|

Recombination in Radar Meteors

Abstract: Recombination of the Electrons in the ionized column has often been considered (see, for example, Öpik, 1955), but the uncertainties in the atomic and molecular species present and in the rate constants have made it difficult to predict. Furthermore, recombination has not been recognized in the observations, so that it has been judged to be negligible (McKinley, 1961). More recently, however, a relatively high rate constant has been found for dissociative recombination of certain molecular ions. We have now ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It is itself a function of time due to atmospheric diffusion effects (both molecular-laminar or turbulent eddy mixing processes can act on the initial trail depending on a number of factors, including the altitude, bolide kinetic energy, entry angle, depth of penetration, etc.). Following Southworth (1973), Bronshten (1983), and Ceplecha et al (1998) we define the initial radius of the meteor trail (found by radar methods as a distance scale about the trail prior to the establishment of thermal equilibrium with the immediate surroundings) in cgs units,…”
Section: Discussionmentioning
confidence: 99%
“…It is itself a function of time due to atmospheric diffusion effects (both molecular-laminar or turbulent eddy mixing processes can act on the initial trail depending on a number of factors, including the altitude, bolide kinetic energy, entry angle, depth of penetration, etc.). Following Southworth (1973), Bronshten (1983), and Ceplecha et al (1998) we define the initial radius of the meteor trail (found by radar methods as a distance scale about the trail prior to the establishment of thermal equilibrium with the immediate surroundings) in cgs units,…”
Section: Discussionmentioning
confidence: 99%